1995
DOI: 10.1113/jphysiol.1995.sp020676
|View full text |Cite
|
Sign up to set email alerts
|

The role of glutamate and GABA receptors in the generation of dorsal root reflexes by acute arthritis in the anaesthetized rat.

Abstract: 1. In rats anaesthetized with pentobarbitone sodium, a unilateral acute arthritis was produced by the injection of kaolin and carrageenan into one knee‐joint cavity. Four hours after injection, the medial articular nerve (MAN) was sectioned distally and recordings obtained from the proximal stump of the nerve. 2. Centrifugally conducted action potentials were recorded from the cut MAN following the development of arthritis. Acute dorsal rhizotomy, but not sympathectomy, prevented the action potentials, and so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(53 citation statements)
references
References 39 publications
1
49
0
3
Order By: Relevance
“…Because resiniferatoxin treatment does not desensitize sympathetic fibers (Cervero and McRitchie, 1982), these were ruled out as being solely responsible for the cystitis. Whether sympathetic innervation is necessary to produce inflammation along with sensory innervation remains unresolved (Heller et al, 1994;Sluka et al, 1994;Rees et al, 1995). Even in light of the preventative effects of hypogastric or intermesenteric nerve section on the development of cystitis, the present study cannot provide conclusive evidence, because sectioning these nerves removes sympathetic as well as some sensory bladder afferents (Neuhuber, 1982;Baron and Jänig, 1991).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Because resiniferatoxin treatment does not desensitize sympathetic fibers (Cervero and McRitchie, 1982), these were ruled out as being solely responsible for the cystitis. Whether sympathetic innervation is necessary to produce inflammation along with sensory innervation remains unresolved (Heller et al, 1994;Sluka et al, 1994;Rees et al, 1995). Even in light of the preventative effects of hypogastric or intermesenteric nerve section on the development of cystitis, the present study cannot provide conclusive evidence, because sectioning these nerves removes sympathetic as well as some sensory bladder afferents (Neuhuber, 1982;Baron and Jänig, 1991).…”
Section: Discussionmentioning
confidence: 72%
“…Although there is no previous disease model in which the CNS is the primary initiator of peripheral inflammation, there is ample evidence of spinally mediated neurogenic inflammation induced by a stimulus to a distant body area (Denko and Petricevic, 1978;Levine et al, 1985a,b;Kolston et al, 1991;Bileviciute et al, 1993;Wesselmann and Lai, 1997). Accordingly, modulation of spinal non-NMDA, GABA-A, A 1 adenosine, or nicotinic receptors reduces peripheral inflammation (Miao et al, 1992;Rees et al, 1994Rees et al, , 1995Rees et al, , 1996Bong et al, 1996). Abnormal activity of spinal interneurons would result in activation of the central branch of primary sensory afferents, leading to increased peripheral release of proinflammatory neuropeptides Rees et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the antiinflammatory effects of intrathecal glutamate receptor antagonists, others have reported that CNQX reduces carrageenan-induced knee edema whereas NMDA receptor antagonists were ineffective (36). This has been ascribed to CNQX-sensitive dorsal root reflexes generated in response to acute arthritis and leading to peripheral substance P release (37,38), which would potentiate edema formation. It is unlikely that a similar mechanism underlies the present findings, since (a) we saw no effects of intrathecal CNQX, and (b) substance P levels remained unchanged in animals treated with NMDA antagonists even though potent antiinflammatory effects were seen.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism, which is insensitive to NMDA receptor antagonist, is quite distinct from the neutrophil-dependent skin lesion model described above and is likely related to CNQXsensitive dorsal root reflexes. This neuronal arc, resulting in efferent activation of peptidergic C fibers, generates peripheral substance P release (20,21), which mainly increases vascular permeability independent of neutrophil activation. Therefore, knee edema can be decreased by stabilizing capillary endothelium rather than by inhibiting neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 99%